Does CEO Ownership Matter in Malaysian Government-controlled Firms' Performance? - Irene, Wei Kiong Ting; Noor Azlinna, Azizan; Qian, Long Kweh (Inderscience Enterprises Ltd., 2015)
This paper examines the relationship between chief executive officers (CEO) ownership, governmental control and firm performance as well as the moderating effect of government-linked companies (GLCs) on the relationship between CEO ownership and firm performance in Malaysian listed companies. Using an unbalanced panel data for the period from 2003 to 2010, this study develops two ordinary least squares regression models. The main findings of the analysis indicate that CEO ownership and governmental control have significantly positive impacts on Tobin's Q. Our result also reveals that governmental control as moderating variable has strengthened the relationship between CEO ownership and performance. The results support the agency theory (Jensen and Meckling, 1976) which argues that agency conflict arises because of the managers' self-interest behaviour. Managers may have personal goals that compete with the owner's goal in maximising shareholders' wealth.